Intra-abdominal corpus alienum - Rodríguez, Gustavo; Ruso, Luis; Bruno, Gerardo; Balboa, Oscar (Cirugía del Uruguay, 1997)
Intraabdominal foreign bodies which can inadvertently be left after surgery are a serious problem which is nevertheless underanalysed in medical literature.